2023
DOI: 10.7759/cureus.46590
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Awareness of and Attitudes Toward Epistaxis

Khalid M Alkhalifah,
Norah I Alhumaidan,
Turki A Alotaibi
et al.

Abstract: Epistaxis, commonly known as nasal bleeding, ranks among the most prevalent emergencies encountered in otorhinolaryngology. The etiology of epistaxis is multifaceted, arising from both local and systemic factors. In Saudi Arabia, a country with a relatively high prevalence of epistaxis, understanding the level of awareness and attitudes toward first aid management of epistaxis is of paramount importance. This systematic review aims to bridge this knowledge gap by evaluating the awareness of and attitudes towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Also, the present findings agree with the meta-analysis done by Alkhalifah et al, in which they found that "the average awareness level of epistaxis and its management was approximately 63%, indicating a moderate level of awareness among Saudi residents". The researchers concluded that "gender, prior knowledge, and profession were significant factors that could influence the levels of awareness observed in their analysis" [27].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the present findings agree with the meta-analysis done by Alkhalifah et al, in which they found that "the average awareness level of epistaxis and its management was approximately 63%, indicating a moderate level of awareness among Saudi residents". The researchers concluded that "gender, prior knowledge, and profession were significant factors that could influence the levels of awareness observed in their analysis" [27].…”
Section: Discussionmentioning
confidence: 99%